2008
DOI: 10.1523/jneurosci.1957-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Reverse of Age-Dependent Memory Impairment and Mitochondrial DNA Damage in Microglia by an Overexpression of Human Mitochondrial Transcription Factor A in Mice

Abstract: Mitochondrial DNA (mtDNA) is highly susceptible to injury induced by reactive oxygen species (ROS). During aging, mutations of mtDNA accumulate to induce dysfunction of the respiratory chain, resulting in the enhanced ROS production. Therefore, age-dependent memory impairment may result from oxidative stress derived from the respiratory chain. Mitochondrial transcription factor A (TFAM) is now known to have roles not only in the replication of mtDNA but also its maintenance. We herein report that an overexpres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
134
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 159 publications
(139 citation statements)
references
References 44 publications
3
134
0
2
Order By: Relevance
“…Similar reductions in the mtDNA copy number were reported for human immunodeficiency virus patients who were treated with nucleoside reverse transcriptase inhibitors and developed type 2 diabetes 13) . Similarly, increased mtDNA copy number via the over-expression of mitochondrial transcription factor A is proposed to serve in the defence of myocytes against cardiac failure 14) and of neurons against age-dependent memory impairment 15) . Thus, maintenance of a relatively high mtDNA copy number therefore appears to represent a physiologic process designed for tissue protection.…”
Section: Discussionmentioning
confidence: 99%
“…Similar reductions in the mtDNA copy number were reported for human immunodeficiency virus patients who were treated with nucleoside reverse transcriptase inhibitors and developed type 2 diabetes 13) . Similarly, increased mtDNA copy number via the over-expression of mitochondrial transcription factor A is proposed to serve in the defence of myocytes against cardiac failure 14) and of neurons against age-dependent memory impairment 15) . Thus, maintenance of a relatively high mtDNA copy number therefore appears to represent a physiologic process designed for tissue protection.…”
Section: Discussionmentioning
confidence: 99%
“…An inhibitory effect of TNF-␣ on LTP has also been reported (Butler et al, 2004;Cumiskey et al, 2007;Tancredi et al, 1992) and it has been identified as a key mediator in the inhibitory effect of A␤ on LTP (Rowan et al, 2007). Recent evidence has indicated that when inflammatory and oxidative stress are inhibited by overexpression of mitochondrial transcription factor A (TFAM), the age-related decrease in LTP in CA1 is ameliorated (Hayashi et al, 2008), while eicosapentaenoic acid, which exerts anti-inflammatory and antioxidative effects similarly restores LTP in aged rats Martin et al, 2002).…”
Section: Introductionmentioning
confidence: 95%
“…Mitochondrial transcription factor A (TFAM), is involved in mtDNA maintenance, including nucleotide formation, mtDNA stabilization and transcription [11]. Recent studies indicated that TFAM and PGC-1 over-expression may inhibit mitochondrial ROS generation and improve mitochondrial respiratory function [12,13]. Furthermore over-expression of TFAM has been shown to protect mitochondria against Aβ-induced oxidative damage in neurons [14].…”
mentioning
confidence: 99%
“…First, as a member of the high-mobility group of protein, TFAM could cover the entire region of mtDNA to form the nucleoid structure, protecting mtDNA from oxidative or inflammation modifications [11,13]. Second, TFAM could maintain mtDNA copy number by binding mtDNA in the form of the nucleoid structure [21].…”
mentioning
confidence: 99%